14C Chronostratigraphy for Qinghai Lake in China. Issue 1 (2014) - Zhou, Weijian; Cheng, Peng; Jull, A J Timothy; Lu, Xuefeng; An, Zhisheng; Wang, Hao; Zhu, Yizhi; Wu, Zhenkun
Abstract : Radiocarbon accelerator mass spectrometry (AMS) techniques were used to date total organic carbon and plant seeds in the lFs core sequence (36°48′N, 100°08′E) from Qinghai Lake, China. This core was drilled ∼18 m into Qinghai Lake sediments as part of an international cooperative research project, "Scientific Drilling at Qinghai Lake in the Northeastern Tibetan Plateau: High-Resolution Paleoenvironmental Records of Eastern Asia Linked to Global Change, " which began in 2004. Based on the differences in lithology and total organic content (TOC) in core lFs, the core was divided into 3 sections for age-modeling purposes: the upper ∼499 cm lacustrine silty clay to clay; the middle unit of silty clay with silt layers from 499–901 cm; and the lower 901–1861 cm silty clay, loess-like silt, and fine sand layers. Three different approaches are applied to the reservoir age problem. First, a simple linear regression gives an offset of 1342 yr. If the core is divided into three sections, linear regressions can be applied separately for the three segments, which results in an age estimate for the average hardwater effect of ∼135 yr BP for the surface section up to 499 cm. If extrapolated for deeper sections, these results imply a higher reservoir offset for those two sections, which may be as much as 1143 and 2523 yr, but this assumes that there are no discontinuities in the core. A third approach using a wiggle-matching approach gave an offset of 196 yr. This study concludes that the reservoir age of Qinghai Lake is complex, but these new data add to our understanding of the 14 C chronology of Qinghai Lake for the last 32 ka.